Resources of Thomson Reuters (Web of science) and Springer Link (Springer-Nature) in the National Medical Holding in 2015: comparative statistics using - Kuat Oshakbayev; Tlektes Maulenkul; Samal Duysekova (National Scientific Medical Center, 2016)
Purpose: To study and analyze a comparative using of web-resources in WebOfScience (Thomson Reuters) и SpringerLink (Springer-Nature) by researchers from JSC «National medical holding» (hereafter - NMH) with its subsidiaries in 2015. Methods: Different reports from the databases and activity of NMH with its subsidiaries in 2015 were used for the analysis. Research collection, inductive analysis, Microsoft Office, biostatistics methods were used. Results: Using statistics by NMH's employers shows that an amount of the requests to use WebOfScience are a twice more than the entrances to. Whereas, the amount of the requests to use SpringerLink source are a ten times more than the entrances to. At the same time, significant difference between the amount of using of SpringerLink and WebOfScience resources is not so valuable. The amount of using the resources is increasing in June-July and November months. The more research organization carries out the number of research projects, the more the organization's researchers need to use the databases. To carry out research projects necessary to use about 106 abstracts from WebOfScience resource and 190 publications (articles) from Springer Link resource per year. Conclusion: The databases of WebOfScience (Thomson Reuters) and SpringerLink (Springer-Nature) are a need for implementing of research projects, and they increase in publications own results of researchers in impact-factor journals.